IDENTIFIKASI FAKTOR PENYEBAB KEMISKINAN DI KOTA SEMARANG DARI DIMENSI KULTURAL - Tri Wahyu Rejekiningsih (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2011)
This research is used to describe and identify the characteristics of poor people in Semarang. We select poor people from 4 villages in Semarang as sample, Bubakan, Krobokan, Genuksari, and Tandang village. In general, factors that cause poverty can be divided into 3 dimensions, natural, structural, and cultural factors. Poverty studies in this research will be analyzed by Cultural dimension approach. From the result we know that the characteristics of poor people in Semarang, are: most of the households’ leaders are low educated (elementary graduated), work as labors, and have some responsibilities to three persons. Besides, we know that there is no equal level on support distribution to poor people. Related to the analysis from cultural dimensions, we know that in Semarang, poor people have cultural value orientations and positive behaviors to see the real life, real work, real time, and the connections between nature and human.